(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Mono pulse receivers have become integral components in angle tracking systems employed in ground-based, airborne radars, and communication setups. Existing literature has extensively discussed the deviations in open-loop angular measurements relative to the antenna’s bore sight axis. However, this paper delves into a comprehensive exploration of deliberate noise interference originating from the target platform, which leads to angular errors. The primary focus is on understanding the intricate interplay between the sum and difference channel noise, in conjunction with interfering noise from the target platform, while placing special emphasis on Mono pulse receiver channel imbalances. In scenarios where there exists an imbalance in Mono pulse receiver channels, both the sum and difference channel noise, along with interfering noise from the target platform, can collectively contribute to angular errors. Conversely, in the absence of channel imbalance (as found in ideal conditions), noise interference does not possess the capability to induce angular errors, regardless of the interfering noise power. This investigation is contextualized within a two-horn Mono pulse system, which is a representative and commonly encountered scenario. Through our analysis, we uncover that channel imbalances within the Mono pulse receiver system can exacerbate open-loop angular errors when exposed to noise interference.